Reviewing the determinants to green purchase: application of the elaboration likelihood model, heuristic-systematic model and nudge - Koh, Wenny Jia-Hui (2017)
This paper adds to the existing literature on green purchase behavior by reviewing the determinants to green purchasing, with the aim of providing insights on their application to green marketing strategies and the store environment. The determinants to green purchasing are identified based on their ability to influence (i) consumer attitudes towards green consumption behaviour and (ii) the decision making process of purchase. In identifying the determinants to attitude towards green consumption, the paper will review classical attitude change models - Elaboration Likelihood Model (ELM) and the Heuristic-Systematic Model (HSM). Noting that there exists an attitude-behaviour gap, the paper proposes the additional review of the Nudge